Development of ZnSxSe1-x nanocrystals with improved physical and optical properties obtained by the combustion synthesis method - Plakhtii, Ye. G.; Hlushkova, D. B.; Volchuk, V. M. (Харківський національний автомобільно-дорожній університет, 2023)
All compounds of ZnSxSe1-x nanocrystals were created by combustion synthesis method. The obtained samples were discovered to have diameters of 55 ± 5 nm and to have a heterogeneous crystalline structure. The fraction of the cubic phase grew in the appropriate ratios as the x value increased, but the fraction of the hexagonal phase in nanocrystals declined from 65 ± 5% to 30 ± 5%. According to XRD data, Mn2+ impurity ions are not mixed in the immediate environment despite the creation of ZnSxSe1-x solid solutions. The Mn2+ ions were surrounded by sulfur ions at a value of 0.2 < х ≤ 1 and selenium ions were at a value of x ≤ 0.2.
Keywords: ZnSxSe1-x nanocrystals; combustion synthesis; X-ray diffraction analysis; crystal structure; EPR spectra; 536.46 + 620.3